Biomodulation in the treatment of oral mucositis: An integrative review (Research, Society and Development, 2024)
This integrative review aim to analyze scientific articles that related the use of biomodulation in the treatment of cancer patients with oral mucositis. The databases accessed were: Scielo; Google academic. The collection followed 6 stages. The first is the theme relate to objectives; second determination of inclusion/exclusion criteria; third collection and stratification of information; fourth methods assessment; fifth interpretation of results, discussion and conclusion. Of these, 30 articles were identified, similar articles, those that did not meet the eligibility criteria and those that did not meet the project standards were excluded, and 10 articles were selected. The delimitation of the research nscope began in 2006, as it was a study with a defined time limit, for the search to be carried out, it was decided to restrict the search until the end of 2023. Biomodulation in the treatment of patients oncology patients with oral mucositis, resepecting comparative criteria between objectives, thematic associations and conclusions; according to the sequence: Authors/year/study design, objectives/correlations and associations/conclusions. In conclusion, oral mucositis is one of the most common side effects in patients  receiving chemotherapy or radiotherapy treatment. The results obtained showed that low-level laser therapy I effective in preventing and treating oral mucositis, reducing pain, inflammation and accelerating healing time.